PENGARUH PENGETAHUAN BUSANA TERHADAP GAYA BERBUSANA PADA MAHASISWI DI ASMADEWA YOGYAKARTA - Yati, Indri; Enggar Kartikasari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2024)
This study aims to determine: (1) the influence of fashion knowledge on female students' dress styles; (2) the level of knowledge of female students; and (3) female students' dress styles at Asmadewa Yogyakarta. The hypothesis of this study is that fashion knowledge influences the fashion style of female students at Asmadewa Yogyakarta. This type of research is descriptive quantitative. The subjects of this study were 58 female students at Asmadewa. Methods of data collection using questionnaires and documentation. Data analysis techniques using descriptive and hypothesis testing using Product Moment correlation. The results showed that: 1) there was a positive and significant influence between knowledge of clothing and the style of dress for female students at Asmadewa with a rcount of 0.796 > rtable of 0.258, the R2 = 63.4%, 2) Asmadewa female students' dress knowledge was in the moderate category with a relative frequency of 55%, 3) Asmadewa female students' dress styles were in the high category with a relative frequency of 48%.